Teste de desempenho escolar no ensino fundamental de Rondônia: idade, nível escolar e socioeconômico, QI e hábitos de leitura e escrita - Pereira, Aparecida de Fátima Gavioli Soares (2020)
This doctoral test aims to know the School Performance Test (TDE) and can influence the teaching and learning process when analyzing individual factors such as age, IQ, sex and socio-cultural aspects, such as years of schooling, frequency of habits parents' reading and writing skills, socioeconomic level, or how much the teachers who work with the students surveyed, understand the school performance test and are committed to the learning results. . The general objective describes analyzing and describing how the process of reading, writing, sum of socio-cultural factors and individuals can contribute to the learning process. The method will be empirical / deductive, with quantitative research, of Observational Procedure, with finite probabilistic, cross-sectional, correlational and comparative designs. The TDE will consist of (individual reading + 10 math items + writing (dictation) and other arithmetic items that will be collective). The tests were applied to 500 schoolchildren, from the 2nd to the 5th year of the fundamental phase of elementary school, preferably 50% female and 50% male. In the end, it intends to contribute to the characterization of a map that demonstrates through the application of neuropsychological assessment and knowledge about the importance of EF, or TDE II may be a standardized test for public education in northern Brazil and its mandatory use in municipality Cacoal, Rondônia.